The predictive value of noninvasive serum markers of liver fibrosis in patients with chronic hepatitis C - Gökcan, Hale; Kuzu, Ufuk Barış; Öztaş, Erkin; Saygılı, Fatih; Öztuna, Derya; Suna, Nuretdin; Tenlik, İlyas; Akdoğan, Meral; Kaçar, Sabite; Yalın Kılıç, Zeki Mesut; Kayaçetin, Ertuğrul (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: This study aims to show the predictive value of noninvasive serum markers on the hepatic fibrosis level. Materials and Methods: This cross sectional study involves 120 patients with chronic hepatitis C. The noninvasive markers used were as follows: age-platelet index (AP index), cirrhosis discriminant score (CDS), aspartate aminotransferase (AST)-alanine aminotransferase (ALT) ratio (AAR), fibrosis-4 (FIB-4) index, AST-platelet ratio index (APRI), Goteborg University Cirrhosis Index (GUCI), FibroQ, King’s score, platelet count. Concurrent liver biopsies were evaluated using the modified Ishak and Knodell scoring systems. In accordance with the Knodell scores, F3-F4 scores were defined as “severe fibrosis,” and the modified Ishak scores stage of ≥3 (F3–F6) were defined as “clinically significant fibrosis.” Receiver Operating Characteristic (ROC) curve analyses were carried out to compare the noninvasive markers with hepatic fibrosis level. Results: Mean age of the patients was 51.7±11.6. A total of 10 patients (8.3%) with Knodell scores and 24 patients (20%) with modified Ishak scores were evaluated to have ≥F3 hepatic fibrosis. ROC analyses with the Knodell and modified Ishak scores were as follows: AP index=0.61–0.57, CDS=0.66–0.55, AAR=0.60–0.49, FIB-4=0.70–0.68, APRI=0.67–0.72, GUCI=0.66–0.72, FibroQ=0.64–0.54, King’s score=0.68–0.54, platelet count=0.61–0.55. Conclusion: We found that APRI, FIB-4, King’s score, and GUCI can be used to determination patients with mild fibrosis with a high negative predictive value and in the differentiation of severe/significant fibrosis from mild to moderate fibrosis.